Derrida’s Turn to Franciscan Philosophy - Marko Zlomislic (Kritike: An Online Journal of Philosophy, 2008)
Contemporary French philosophers such as Levinas, Bataille, and Derrida, along with the existentialists Kierkegaard and Nietzsche have all made use of Franciscan insights in order to safeguard the ipseity that cannot be reduced or totalized. In keeping with the taste that concerns me, this paper will examine Derrida’s turn to the poetry of Gerard Manley Hopkins and how such a turn may place Derrida within a catholic and Franciscan tradition.